Management for receiving antibiotics in sepsis patients in the Emergency Department: a situational analysis - T, Chounjai; A, Sukonthasarn; S, Wangsrikhun (Biomedical Sciences and Clinical Medicine, 2021)
Objectives To analyze the situation regarding management for receiving antibiotics among sepsis patients in the emergency department (ED) in a tertiary care hospital. Methods This study used the Donabedian Nursing Quality Assessment Model (Donabedian, 2002) as conceptual framework. This model composes of structure, process and outcomes. Samples consisted of 2 groups: The first group was the 306 accessible medical records of patients with sepsis who were treated in the ED from July, 2018–June, 2019 and the second group was 40 health personnel who involved in management the patients in the first group. Data were analyzed using descriptive statistics and content categorization. Results The results of this study were as follows: Structure that 1)The agency had a clearly established policy regarding management quality indicator for receiving antibiotics in sepsis patients including standard guidelines for implementation, Sepsis Fast Track development, quality indicators for setting and monitoring, and policy deployment through various channels as well as for regularly reviewing improvement 2)The agency had manpower management for physicians, nurses, medical laboratory technologists, and pharmacists, but still not have enough manpower at all time, especially nurses 3)The agency’s multidisciplinary working system was not clearly established and 4)Material and medical supplies were mostly well prepared, but there was a limitation of ED antibiotics supplied which caused delayed management if needed antibiotics were not supplied. The process showed the average time for each of the process were as followings: 1)The average time used for the screening process was 1.48 minutes 2)The average time used for the diagnostic process was 120.07 minutes 3) The average time used for the treatment process was 10.34 minutes and Outcomes: showed the average time for each of the process were as followings: 1)The average time for receiving antibiotics among sepsis patients was 82.39 minutes 2)The number of patients receiving antibiotics within 60 minutes was 149 (48.69%) 3)The number of patients who developed septic shock was 64 (20.92%) and 4)The number of patients who died within 72 hours after receiving ED care was 32 (10.46%). Conclusion Results from this study can be used as input for quality development regarding management for receiving antibiotics in sepsis patients in the emergency department in this tertiary care hospital in order to aim for more positive outcomes.